Candidate perceptions of the UK Recorded Consultation Assessment: cross-sectional data linkage study. Issue 1 (2nd January 2022) - Botan, Vanessa; Laparidou, Despina; Phung, Viet-Hai; Cheung, Peter; Freeman, Adrian; Wakeford, Richard; Denney, Meiling; Law, Graham R; Siriwardena, Aloysius Niroshan
ABSTRACT: The Recorded Consultation Assessment (RCA) was rapidly developed to replace the Clinical Skills Assessment (CSA) for UK general practice licencing during COVID-19. We aimed to evaluate candidate perceptions of the RCA and relationships with performance. We conducted a cross-sectional survey of RCA candidates with attitudinal, demographic, and free text response options, undertaking descriptive and factor analysis of quantitative data with qualitative thematic analysis of free text. Binomial regression was used to estimate associations between RCA pass, candidate characteristics and questionnaire responses. 645 of 1551 (41.6%) candidates completed a questionnaire; 364 (56.4%) responders permitted linkage with performance and demographic data. Responders and non-responders were similar in exam performance, gender and declared disability but were significantly more likely to be UK graduates (UKG) or white compared with international medical (IMG) or ethnic minority graduates. Responders were positive about the digital platform and support resources. A small overall majority regarded the RCA as a fair assessment; a larger majority reported difficulty collecting, selecting, and submitting cases or felt rushed during recording. Logistic regression showed that ethnicity (white vs minority ethnic: odds ratio [OR] 2.99, 95% confidence interval [CI] 1.23, 7.30, p = 0.016), training (UK vs IMG: OR 6.88, 95% CI 2.79, 16.95, p < 0.001), and English as first language (OR 5.11, 0% CI 2.08, 12.56, p < 0.001) were associated with exam success but questionnaire subscales, consultation type submitted, or extent of trainer review were not. The RCA was broadly acceptable but experiences were variable. Candidates experienced challenges and suggested areas for improvement.